Proportion and Potential Risk Factors of Poor Glycemic Control among Patients with Type 2 Diabetes Mellitus: Experience of a Tertiary Center in Baghdad, Iraq, 2020 - Zaboon Al-Majidi, Zahraa A.; Lami , Faris H.; Hakimi, Sevil (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Diabetes Mellitus is the most prevalent metabolic disorder worldwide. Effective diabetes self-management and keeping the Glycosylated hemoglobin level within the normal range could decrease the burden on the health system by reducing hospital admissions and diabetic complications, lowering the financial strain on the health system. Objective: To recognize the potential risk factors of poor glycemic control in patients having type 2 Diabetes Mellitus in Baghdad, Iraq. Patients and Methods: This cross-sectional study was conducted in the Diabetes and Endocrine Center at Al-Kindy Teaching Hospital, Baghdad, Iraq, from June to November 2020. The total number of the study’s participants was 234. Based on the cutoff point of glycosylated hemoglobin of 7, the patients with glycosylated hemoglobin of ≥7 were considered uncontrolled, and those with glycosylated hemoglobin of <7 were considered controlled. Results: The proportion of cases with uncontrolled diabetes was 68.4% (160). The remaining 74 patients had controlled diabetes. Age, sex, marital status, and employment status were not significantly associated with the control status (P>0.05). The binary analysis showed a significant association observed between the control status and level of education (P=0.001), income (P=0.001), presence of comorbidities (P=0.028), positive family history (P=0.03), dyslipidemia (P=0.001), cholesterol level (P=0.002), high triglyceride level (P=0.001), and low-density lipoprotein-cholesterol level (P=0.025). The smoking status, body mass index, and high-density lipoprotein-cholesterol level were not significantly associated with the control status (P>0.05). The disease characteristics, including the disease duration, fasting blood glucose, type of medication, self-monitoring, healthy diet, physical activity, and medication adherence, were significant factors (P<0.001). The multivariate regression method showed that dyslipidemia, FBS≥130, physical inactivity, and poor medication adherence were significant predictors for uncontrolled DM (P-value = 0.03, 0.001, 0.03, and 0.043, respectively). Conclusion: The most important potentially modifiable risk factors for poor diabetes control were dyslipidemia, physical inactivity, and poor adherence to the management protocol. Enhancing the education of patients and their healthcare providers on these factors is crucial to improving the patients’ control status.